Attracting, Training, and Retaining a Skilled and Ready Workforce to Support Maine’s Seafood Economy - Kaczor, Keri; Noll, Anne (Maine Policy Review, 2023)
Despite the many challenges, the entirety of Maine’s seafood economy—from harvesting, transportation and logistics, marketing, and food service—still offers valuable employment and career opportunities. Understanding training needs and career aspirations, as well as how they align to available training and career opportunities is key to addressing the challenges of recruiting, training and retaining a skilled and ready workforce. Findings from recent projects assessing workforce training needs, preferred training formats, existing workforce barriers, and incentives will be shared as well as input from educators and others who support the industry. Recommendations for investment and new programs to support the industry include: providing hands-on, experiential learning and mentorship provided by trusted entities; teaching relevant technical and life skills that are transferable across industries; essential for year-round employment rather than seasonal; offering training that allows versatile participation that is short-duration, aligned with seasonal fishing/aquaculture activities; the provisions of tangible incentives; and the need for developing career inspirations early and often (K-8). Further, providing mental and physical health support, enabling diversity, equity, and inclusion in the industry, and ensuring that educators have the tools and resources to successfully teach are integral pieces of a successful future workforce.
Keywords: Workforce; Maine; Seafood Economy